Macroprudential Policy in the New Keynesian World - Hans Gersbach; Volker Hahn; Yulin Liu (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We integrate banks and the coexistence of bank and bond financing into an otherwise standard New Keynesian Framework with capital, and derive the microfounded, bank-augmented IS and Phillips Curves for the corresponding two-sector economy. We study the interplay of monetary and macroprudential policies. We examine how policy-making could be operationalized by loss functions for monetary and macroprudential policy-making. Finally, we investigate the optimal institutional structures.
Keywords: E52; E58; G28; 330